1993
DOI: 10.1093/ajcn/57.6.868
|View full text |Cite
|
Sign up to set email alerts
|

Meal-frequency effects on plasma hormone concentrations and cholesterol synthesis in humans

Abstract: To examine meal-frequency effects on circulating hormone concentrations and cholesterol synthesis, male subjects consumed liquid diets given as either six evenly spaced (ES) or three diurnal (DI) meals over 3 d. Deuterium oxide was given on day 2 and blood sampled every 4 h over days 2 and 3 to measure plasma cholesterol, glucose, insulin, and glucose-dependent insulinotropic polypeptide (GIP) concentrations and cholesterol synthesis. Cholesterol synthesis was determined from deuterium incorporation into plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 30 publications
5
51
1
2
Order By: Relevance
“…However, it has been shown that neither fat nor protein in the amounts found in most foods (with the exception of peanuts and most nuts) Lower postprandial glucose rise (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Reduced daily mean insulin levels (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Flatter gastric inhibitory polypeptide response (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993) Decreased 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992 Prolonged suppression of plasma free fatty acids (Jenkins et al, 1990) Reduced urinary catecholamine output (Jenkins et al, 1990) Lower total and LDL cholesterol levels (Jenkins et al, 1989Arnold et al, 1993;Cohn 1964) Reduced hepatic cholesterol synthesis (Jones et al, 1993) Decreased serum apolipoprotein B levels (Jenkins et al, 1989) Decreased serum uric acid levels Raised urinary uric acid excretion Adapted from Jenkins et al (1995). Glycemic index in chronic disease LS Augustin et al significantly alters the glycemic response (Wolever et al, 1994).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown that neither fat nor protein in the amounts found in most foods (with the exception of peanuts and most nuts) Lower postprandial glucose rise (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Reduced daily mean insulin levels (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Flatter gastric inhibitory polypeptide response (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993) Decreased 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992 Prolonged suppression of plasma free fatty acids (Jenkins et al, 1990) Reduced urinary catecholamine output (Jenkins et al, 1990) Lower total and LDL cholesterol levels (Jenkins et al, 1989Arnold et al, 1993;Cohn 1964) Reduced hepatic cholesterol synthesis (Jones et al, 1993) Decreased serum apolipoprotein B levels (Jenkins et al, 1989) Decreased serum uric acid levels Raised urinary uric acid excretion Adapted from Jenkins et al (1995). Glycemic index in chronic disease LS Augustin et al significantly alters the glycemic response (Wolever et al, 1994).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Increasing meal frequency in isocaloric diets in diabetic and non-diabetic subjects has been shown to reduce postprandial glucose rise (Jenkins et al, 1992, Bertelsen et al, 1993Jones et al, 1993), daily insulin levels (Jenkins et al, 1992;Bertelsen et al, 1993;Jones et al, 1993) and 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992. Increasing meal frequency is now included in the recommendations given for the management of diabetes by the American Diabetes Association (1994).…”
Section: Glycemic Index In Chronic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The reduced diet-induced thermogenesis with the irregular meal frequency may lead to weight gain in the long term (102) . With a regular meal frequency glucose excursions are blunted, net insulin production is reduced, and LDLcholesterol concentrations tend to be lowered, mainly due to gastric emptying slowing down, and insulin production being reduced (103)(104)(105)(106)(107)(108)(109)(110)(111) . The net result is that lipid oxidation is favoured at the expense of glucose oxidation and lipid storage, and cholesterol synthesis is reduced.…”
Section: Circadian Misalignment and Sleepmentioning
confidence: 99%
“…This may reduce adiposity and the level of circulating fatty acids, thereby leading to systematic, adaptive changes in both lipid and carbohydrate metabolism. Also examples of long-term responses to a sustained regular meal frequency such as improved glucose tolerance, and moderately reduced fasting plasma total and LDL-cholesterol, and a higher HDL:LDL cholesterol ratio are observed in normolipidaemic free-living subjects, as well as in type-II diabetes patients (103)(104)(105)(106)(107)(108)(109)(110)(111) . Also for cholesterol synthesis, meal frequency-dependent control of cholesterogenesis appeared to be mediated via hormonal mechanisms (97) .…”
Section: Circadian Misalignment and Sleepmentioning
confidence: 99%